Character types analysis of Heaven Official’s Blessing (book 1) novel by MXTX - Putri, Dwicahya Setia; Wediyantoro, Prilla Lukis (Universitas Merdeka Malang, 2024)
This study presents a focused character analysis of Heaven Official’s Blessing (book 1) by MXTX, a novel set in a fantastical world inspired by Chinese mythology. The narrative centers around Xie Lian, a former crown prince who ascends to become a martial god. The analysis aims to deepen understanding of the character types within the novel as it has only few prior academic studies conducted. By categorizing and examining these character types, the study reveals how each character functions within the story, enriching readers' comprehension of their roles. Character types are divided into two categories: major characters and minor characters. Major characters include the protagonist (Xie Lian), antagonist (Xuan Ji and Kemo), and tritagonist (Fu Yao and Nan Feng). Minor characters include foil (Pei Xiu), static (Ling Wen), dynamic (Pei Ming, Feng Xin, Mu Qing), flat (Tian Sheng, Xiao-Pengtou, Xiao-Ying), round (A-Zhao, Banyue), and stock (Wind Master, Jun Wu). This study has limitations as it focuses solely on character types in Book 1, though the novel spans eight books, leaving many characters and literary elements unexplored. Future studies should fill these gaps with comparative analyses, exploring cultural influences, applying diverse literary theories, and using multidisciplinary approaches.